2023
DOI: 10.3390/molecules28104163
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Various Bioactivity of Acylhydrazone-Containing Matrine Analogues

Abstract: Compounds with acylhydrazone fragments contain amide and imine groups that can act as electron donors and acceptors, so they are easier to bind to biological targets and thus generally exhibit significant biological activity. In this work, acylhydrazone fragments were introduced to the C-14 or C-11 position of matrine, a natural alkaloid, aiming to enhance their biological activities. The result of this bioassay showed that many synthesized compounds exhibited excellent anti-virus activity against the tobacco … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The above results demonstrated that phenylthiazole is a promising antifungal skeleton for discovering new fungicides. Acylhydrazone compounds possess a wide range of biological activities, such as antifungal [19][20][21][22][23][24], antibacterial [25][26][27], insecticidal [28], antiviral [29,30], and antitumor activities [31,32], which have been widely concerned in the field of pesticides and pharmaceuticals. At present, some compounds containing an acylhydrazone structure have been developed as pesticides or pharmaceuticals, such as benquinox (fungicide) [19,25,29], metaflumizone (insecticide) [20,23,29], and nitrofurazone (antibacterial drug) [31].…”
Section: Introductionmentioning
confidence: 99%
“…The above results demonstrated that phenylthiazole is a promising antifungal skeleton for discovering new fungicides. Acylhydrazone compounds possess a wide range of biological activities, such as antifungal [19][20][21][22][23][24], antibacterial [25][26][27], insecticidal [28], antiviral [29,30], and antitumor activities [31,32], which have been widely concerned in the field of pesticides and pharmaceuticals. At present, some compounds containing an acylhydrazone structure have been developed as pesticides or pharmaceuticals, such as benquinox (fungicide) [19,25,29], metaflumizone (insecticide) [20,23,29], and nitrofurazone (antibacterial drug) [31].…”
Section: Introductionmentioning
confidence: 99%
“…Acylhydrazones as reactive groups include both amide and imine structures and therefore can act as both hydrogen bond donors and acceptors. 12 Acylhydrazones have a strong coordination ability and a variety of coordination modes that allow flexibility in the orientation of the acylhydrazone structure in space, 13 so they can easily form stable hydrogen bonds or other interactions with biological targets, increasing the affinity for the receptor and thus affecting its biological activity. 14 The commercially available fungicide benquinox (Fig.…”
Section: Introductionmentioning
confidence: 99%